A comparative study on the effectiveness of calcium chloride and alum as firming agents for mango chutney - Negrido, Rocel M. (1997.)
The effectiveness of calcium chloride and alum as firming agents for mango chutney was compared.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Calcium chloride; Alum; Chutney